2007
DOI: 10.1021/np070061b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Brominated Mono- and Bis-phenols from the Marine Red Alga Symphyocladia latiuscula with Radical-Scavenging Activity

Abstract: Four new highly brominated and fully substituted mono- and bis-phenols, 1-(2,3,6-tribromo-4,5-dihydroxybenzyl)pyrrolidin-2-one (1), 1,2-bis(2,3,6-tribromo-4,5-dihydroxyphenyl)ethane (2), 6-(2,3,6-tribromo-4,5-dihydroxybenzyl)-2,5-dibromo-3,4-dihydroxybenzyl methyl ether (3), and 2,3,6-tribromo-4,5-dihydroxybenzyl methyl sulfone (4), were characterized from the marine red alga Symphyocladia latiuscula. In addition, five known bromophenols, bis(2,3,6-tribromo-4,5-dihydroxyphenyl)methane (5), bis(2,3,6-tribromo-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 12 publications
2
92
0
1
Order By: Relevance
“…Additionally, it was reported that bromophenol 1 is an inhibitor of protein tyrosine phosphatase 9 . Antioxidant activities of 1 and 4 have also been reported 10,11 . Recently, we have achieved an alternative synthesis of 1 10 , first total synthesis of 2, 3, 4 12,13 , and a series of diphenylmethanone like bromophenols 5 10 .…”
Section: Introductionmentioning
confidence: 76%
“…Additionally, it was reported that bromophenol 1 is an inhibitor of protein tyrosine phosphatase 9 . Antioxidant activities of 1 and 4 have also been reported 10,11 . Recently, we have achieved an alternative synthesis of 1 10 , first total synthesis of 2, 3, 4 12,13 , and a series of diphenylmethanone like bromophenols 5 10 .…”
Section: Introductionmentioning
confidence: 76%
“…366 Generally, the DPPH radical-scavenging effects of the bisphenols are stronger than those of the monophenols, suggesting that the free-radical-scavenging activities of these phenolic compounds are correlated with the number of hydroxyl groups in the molecules. 380 Replacement of an OH group with an OMe group on the aromatic ring significantly decreased the activity. 366 Meanwhile, the number and position of the bromine atoms are also important factors contributing to the variation in DPPH scavenging activity observed for the compounds in this class.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Recently, the relative configuration of laurenmariannol (aplysiol B, 368) was revised with the aid of a 1D gradient selective NOESY experiment. 245 .0]undecane unit thereby affording a 7/7/6-ring system, which further connects via single bonds either to an oxolane ring (380) 240 or to an oxepane ring (381−386). 249 In contrast, two other triterpenes, enshuol (387) well as in the sea hare Dolabella auricularia, 252,253 which is known to feed on marine algae like Laurencia species.…”
Section: Halogenated Triterpenes/polyethersmentioning
confidence: 99%
“…On the other hand, 3,4,6-tribromo-5-(2,5-dibromo-3,4-dihydroxybenzyl)benzene-1,2-diol (3) and 5,5'-methylenebis(3,4,6-tribromobenzene-1,2-diol) (4) show aldose reductase inhibitory activity [13]. Furthermore, it is known that 4 exhibits antioxidant activity [14].…”
mentioning
confidence: 99%